Pancreatic cancer in children - Mantero, Manuel; Goluboff de Milies, Rosa; Anavitarte, Eduardo; Arrutti, César; Torres, David (Cirugía del Uruguay, 1972)
One case of primitive pancreatic cancer in a síxyear old girl is described. World literature on the subject is revised and the clínica! and pathological evoIution established.